PENGARUH FINANCIAL STABILITY, FINANCIAL TARGETS, EXTERNAL PRESSURE, INEFFECTIVE MONITORING, DAN CHANGE IN AUDITOR TERHADAP FINANCIAL STATEMENT FRAUD - Helliyana Saputeri; Karunia Zuraidaning Tyas; Aning Fitriana (Perwira Journal of Economics & Business, 2026)
Financial statement fraud is an intentional act committed by company staff that results in the presentation of inaccurate information or the omission of material information in financial reporting. This study aims to empirically examine the effect of financial stability, financial targets, external pressure, ineffective monitoring, and change in auditor on financial statement fraud. The study population was 95 foods and beverages manufacturing companies listed on the Indonesia Stock Exchange from 2021 to 2024. The sample size was 29 companies selected using purposive sampling, resulting in a total sample size 116 over a four-year period. Multiple linear regression analysis was used for data analysis. The results indicate that financial stability, financial targets, external pressure have a positive effect on financial statement fraud, while ineffective monitoring and change in auditor have no effect on financial statement fraud. Therefore, financial stability, financial targtes, external pressure indicate that both internal and external financial pressure can encourage management to commit fraud in financial reporting. Meanwhile, ineffective monitoring and change in auditor require strengthening internal control systems and increasing financial transparency, espicially in situations of high financial pressure, to minimize the risk of financial statement fraud.